2017
DOI: 10.3945/an.116.014852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anthocyanins on Cardiometabolic Health: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Numerous clinical trials have examined the role of anthocyanins on cardiometabolic health, but their effects have not been quantitatively synthesized and systematically evaluated. The aim of our study was to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) assessing the effects of anthocyanins on glycemic regulation and lipid profiles in both healthy populations and those with cardiometabolic diseases. The MEDLINE, EMBASE, Cochrane database, OVID EBM Reviews, and clinicaltri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
106
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 72 publications
6
106
0
2
Order By: Relevance
“…We additionally found that the berries but not the grapes/wine significantly reduced T-C and increased FMD. In agreement with this last result, a recent meta-analysis on 24 RCTs showed that both acute and chronic supplementation with ANC-rich foods or extracts significantly improved FMD and improved wave velocity after acute consumption [21]. …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We additionally found that the berries but not the grapes/wine significantly reduced T-C and increased FMD. In agreement with this last result, a recent meta-analysis on 24 RCTs showed that both acute and chronic supplementation with ANC-rich foods or extracts significantly improved FMD and improved wave velocity after acute consumption [21]. …”
Section: Discussionsupporting
confidence: 60%
“…Previous reviews and meta-analyses of randomized-controlled trials (RCTs) have explored the evidence of the effects of the intake of berry [16,17,18,19,20,21], nut [22,23], pomegranate [24,25], and grape [26,27] foods and (or) derived products on different cardiometabolic risk factors (i.e., serum lipids, blood pressure, glucose). The results of these analyses have indicated inconsistencies in the overall effects and have pointed at potential different responses between different subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…With this objective, a number of recent studies have discussed the interest of including fruits in the human diet, as sources of bioactive phytochemicals, more specifically anthocyanins. Along this line, this strategy is supported by the cumulative data available on the biological effects of these compounds on glycolipid metabolism, reducing fasting and 2 h postprandial glucose, and modulating the level of glycemic biomarkers and low density lipoprotein (LDL) [10,11]. However, the bioavailability of the bioactive polyphenols reported in the literature is low, being estimated to lie in a range between 5% and 10% of the total intake, after intestinal absorption [12].…”
Section: Introductionmentioning
confidence: 97%
“…The dietary intake of ACNs is up to 9-fold higher than that of other dietary flavonoids. Epidemiological studies have found an inverse association between the consumption of ACNs and risk of cardiovascular diseases [1][2][3][4][5][6]. Their role in prevention of cardiovascular disease is strongly linked to the protection against oxidative stress and inflammation [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%